2017
DOI: 10.1097/pec.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Care

Abstract: Objective Every year, emergency medical services agencies transport approximately 150,000 pediatric patients between hospitals. During these transitions of care, patient safety may be affected and contribute to adverse events when important clinical information is missing, incomplete, or inaccurate. Written interfacility transfer policies are one way to standardize procedures and facilitate communication between the hospitals leading to improved patient safety and satisfaction for children and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Genovesi et al 24 reported an increase in the presence of written interfacility guidelines and use of agreements but almost a third of the hospitals in this study do not have any. The literature describes that in hospitals with low and medium ED patient volumes were often lacking of written interfacility transfer guidelines and/or agreements, and in our survey, there is a lack of protocols and regulatory laws.…”
Section: Discussioncontrasting
confidence: 56%
“…Genovesi et al 24 reported an increase in the presence of written interfacility guidelines and use of agreements but almost a third of the hospitals in this study do not have any. The literature describes that in hospitals with low and medium ED patient volumes were often lacking of written interfacility transfer guidelines and/or agreements, and in our survey, there is a lack of protocols and regulatory laws.…”
Section: Discussioncontrasting
confidence: 56%
“…Considering a majority of CAHs in the study are challenged to have necessary resources to sustain care for ill or injured children, having processes in place to transfer a child to the appropriate level of care is essential. 12,32,33 This element of pediatric readiness is an administrative element that potentially has minimal financial burden on a facility. Models of agreements and guidelines exist, as well as models in Arizona that demonstrate their presence can decrease mortality among severely injured children.…”
Section: Discussionmentioning
confidence: 99%
“…Prior analyses of NPRP data demonstrated the importance of pediatric emergency care coordinators (PECCs) on overall pediatric readiness, as well as regional differences in pediatric readiness. [19][20][21][22] However, demographic and hospital characteristics of EDs with pediatric mental health care policies, as well as In line with previous findings showing that rural areas had lower levels of pediatric readiness compared with urban areas, 19 we hypothesized that rural counties would have fewer EDs with a pediatric mental health care policy in place. We also hypothesized that among EDs having PECCs and additional policies in place aimed at addressing children's mental health care needs, including reporting and treating suspected child abuse and neglect, policies for promoting family-centered care, and written guidelines for transfer of children with mental health concerns, would be associated with having a mental health care policy.…”
mentioning
confidence: 56%